2017
DOI: 10.1016/j.chb.2017.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Risk perceptions of cyber-security and precautionary behaviour

Abstract: A quantitative empirical online study examined a set of 16 security hazards on the Internet and two comparisons in 436 UK- and US students, measuring perceptions of risk and other risk dimensions. First, perceived risk was highest for identity theft, keylogger, cyber-bullying and social engineering. Second, consistent with existing theory, significant predictors of perceived risk were voluntariness, immediacy, catastrophic potential, dread, severity of consequences and control, as well as Internet experience a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(47 citation statements)
references
References 58 publications
3
32
0
3
Order By: Relevance
“…First, according to previous work (Adams, 2012), in general when people feel in control they act less cautiously. Our results support this idea (as in the domain of Internet security; Van Schaik et al, 2017), the more a Facebook user felt in control in relation to security-and privacy hazards overall, the less likely they were to have chosen specific safe privacy-and security settings.…”
Section: /50supporting
confidence: 75%
“…First, according to previous work (Adams, 2012), in general when people feel in control they act less cautiously. Our results support this idea (as in the domain of Internet security; Van Schaik et al, 2017), the more a Facebook user felt in control in relation to security-and privacy hazards overall, the less likely they were to have chosen specific safe privacy-and security settings.…”
Section: /50supporting
confidence: 75%
“…In the risk literature and PMT literature, risk perception has often been studied from a cognitive perspective (Loewenstein et al, 2001). Studies consider the impact of threat-related knowledge, voluntariness and control over exposure, newness, catastrophic potential and severity of consequences (van Schaik et al, 2017). Yet cognitive evaluations only partially explain variations in risk perceptions and riskrelated decision-making (Loewenstein et al, 2001).…”
Section: The Affect Heuristic In Cybersecurity Risk Perceptionmentioning
confidence: 99%
“…As such, it is essentially a risk management mechanism. Van Schaik et al [170] identified a number of predictors of precautionary cyber security behaviors. Other researchers have carried out similar studies, also identifying particular predictors [67,79,164,103].…”
Section: Riskmentioning
confidence: 99%